The Electronic Communication Environment Impact - V. P. Terin (Vestnik MGIMO-Universiteta)
What we understand is dependant on how we understand, by what means. With this in mind the electronic communication environment impact can be understood differently. The author singles out and interrelates lineality and simultaneity as the two competing modes of reasoning, whose application leads to strikingly contrasting results. The figure/ground approach, as it is practiced by contemporary researchers, allows to operate in the field more adequately. This fact is very important to know taking into consideration both its managerial potential and the educational promises. To add, the students today are known to be greatly influenced by the synchronous mode of perception and thinking as it is readily offered by electronic gadgets. On the other hand, they are often seen being estranged by the literary establishment's approaches still in use. In other words, there have emerged whole clusters of new problems in this respect both for the teachers and the studies themselves. To deal with them successfully, our task is to increasingly concentrate on renovating our electronic experiences communicating with the students to overcome the forthcoming difficulties in the process of promoting the new educational agenda and getting them adequately prepared for the new challenges of the electronic communication world. At to the notions which may be of great importance with this in mind, they include information retrieval, pattern recognition and interfacing, to name for the beginning just a few of them.